(untitled) (Practitioner Research, 2021)
The primary purpose of action research carried out by teachers is to improve their own educational and pedagogical practices in a specific context. However, teachers need to develop a more critical stance on their practice in order to interrogate and validate their action research in a more systematic way. Literature suggests that action research can be strengthened through the involvement of critical friends who can ask provocative questions, provide data to be examined through another lens, and offer a critique of a person’s work as a friend. This narrative review paper seeks to emphasise the role of critical friends and propose a critical friend framework that can be integrated into action research studies. It extensively reviews the role of critical friends in action research with illustrations from previous studies and offers a critical friend’s protocol according to the action research process of self-reflective cycles, namely reconnaissance, planning, action and observation, and reflection. It is therefore suggested that teachers should consider the incorporation of critical friends into their action research studies.